Sosialisasi Pentingnya Peningkatan Kualitas Produk Serta Layanan di UMKM Untuk Menghadapi Tantangan Digitalisasi - Suriyanti Suriyanti; Novi Fitria Hermiati; Prasetyo Hari Sandi; Arif Widodo Nugroho (Lembaga Pengembangan Kinerja Dosen, 2025)
The business world has undergone a major transformation as a result of the digital era, and this is also true for Indonesian MSMEs. While MSMEs play an important role in the economy, many of them still struggle to adjust to the rapid changes brought about by digital technology. MSMEs must be able to adapt to the increasingly fierce business competition to meet evolving consumer expectations. To stay relevant and compete in a dynamic market, MSMEs must quickly go digital as digitalization increases consumer expectations of service quality and shopping experience. The aim is to provide a Strategy for Improving Product and Service Quality in facing the challenges of digitalization. The method used has three stages, namely preparation, implementation and evaluation. Service activities provide implementation around strengthening digital marketing, product innovation, improving product quality, developing human resources, and opening collaborations with other parties that allow MSMEs to face challenges in this digitalization era. The results obtained are products that are easily accessible, innovative, and of high quality, and can adjust quickly to advances in digital technology.